The Commercial Jar in the Ancient Near East: Its Evidence for Interconnections amongst the Biblical Lands - Raban, Avner (1980)
Ph.D. Thesis; in Hebrew; investigation of provenance based on Neutron Activation Analysis. 195-228: The standard measures and volumes of commercial jars in the ANE; Supervisors: Trude Dothan, Isidore Perlman.